Relationship of Selected Motor Fitness Variables to Playing Ability In Hockey: Examining the Relationship between Motor Fitness and Playing Ability in Hockey (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The purpose of the study was to find out therelationship of selected motor fitness variables to playing ability in hockeyof boys between 14-16 years of age. 60 male hockey players who have at leastrepresented U. P. Sate were acted as subjects for this study. The subject'sperformances was measured for their selected motor fitness variables , whichincluded standing broad jump for muscular endurance, 600 - yard run /walk forcardiovascular endurance , Scott and French test for flexibility , and 50-yardrun speed . Subjects playing ability were measured by the coach who has gradedeach individual player out of 10 points. Statistical analysis of data comprisedof person's product. Moment Correlation to assess the relationship betweenmotor fitness variables and playing in Hockey. The obtained coefficient ofcorrelation for the group was compared by the r. 05 levels of significance.